2009
DOI: 10.1007/s00780-009-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Option hedging for small investors under liquidity costs

Abstract: Following the framework of Ç etin, Jarrow and Protter [4] we study the problem of super-replication in presence of liquidity costs under additional restrictions on the gamma of the hedging strategies in a generalized Black-Scholes economy. We find that the minimal super-replication price is different from the one suggested by the Black-Scholes formula and is the unique viscosity solution of the associated dynamic programming equation. This is in contrast with the results of [4] who find that the arbitrage free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 30 publications
4
73
1
Order By: Relevance
“…In particular, we specify in which way markets are finitely liquid when transaction costs are introduced and the role of transaction costs in determining the size and the frequency of adjustment. Our paper provides results that are consistent with the approach of Cetin et al (see, for example, Cetin et al, 2004;Cetin et al, 2006;Cetin et al, 2007), although they do not deal with models of feedback effects. Instead of concentrating on the feedback effects that govern the dependence of the equilibrium stock price on the portfolio actions of programme traders, as we do in our paper, they have a reduced form illiquidity model, introducing a supply curve which excludes strategic trading and where liquidity costs are increasing in the position to liquidate.…”
Section: Introductionsupporting
confidence: 90%
“…In particular, we specify in which way markets are finitely liquid when transaction costs are introduced and the role of transaction costs in determining the size and the frequency of adjustment. Our paper provides results that are consistent with the approach of Cetin et al (see, for example, Cetin et al, 2004;Cetin et al, 2006;Cetin et al, 2007), although they do not deal with models of feedback effects. Instead of concentrating on the feedback effects that govern the dependence of the equilibrium stock price on the portfolio actions of programme traders, as we do in our paper, they have a reduced form illiquidity model, introducing a supply curve which excludes strategic trading and where liquidity costs are increasing in the position to liquidate.…”
Section: Introductionsupporting
confidence: 90%
“…The consequence is a nonlinear term in the wealth equation and a liquidity premium in option prices. Our analysis also has some common features with the liquidity cost model of [10], and in particular the Taylor expansion of the super-hedging cost of [39] who use the PDE characterisation of [11]. The main difference however is that in these models the price impact is momentary, whereas we regard it as a longer-lasting phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Super-replication cost or related problems were studied in (Cetin, Soner & Touzi, 2010), (Gokay & Soner, 2012), (Dolinsky & Soner, 2012) and (Xing, 2015). In (Cetin, Soner & Touzi, 2010), the existence of the continuous time super-replication cost from a binomial model was shown. (Gokay & Soner, 2012) showed that a stochastic optimal control problem could be seen as a dual of the super-replication problem.…”
Section: Introductionmentioning
confidence: 99%